Follicular Thyroid Carcinoma in a Country of Endemic Iodine Deficiency (1994–2013). (25th February 2018) - Der, Edmund Muonir
Abstract : Background . Follicular thyroid cancer (FTC) has historically been linked to iodine deficiency. Although Ghana is among the iodine deficient regions of the world, the proportions, trends, and the clinical features of FTCs have not been studied as a single disease entity. The aim of this study was to determine the relative frequencies, trends, and the clinicopathological characteristics of FTCs among all thyroid malignancies in our institution. Materials and Methods . This was a retrospective study from January 1994 to December 2013. Data were analysed using SPSS software version 23 (Chicago) and Graph pad prism version 5.00. Results . Follicular thyroid cancer was the second thyroid malignancy (35.0%) and showed a gradual rise in relative proportions over the period. The male-female ratio was 1 : 1.5. The mean ages were 46.9 (SD ±17.3) for males and 46.4 (SD ±13.3) years for females. Enlarged palpable anterior neck swelling was the commonest symptom in males (86.7%) and females (91.3%) (P = 0 . 730 ). Hurthle cell carcinoma was the commonest variant of FTC, with 26.7% males and 10.6% females (P = 0 . 116 ). Distant spread was found in 23.3% of males compared to 19.1% of females (P = 0 . 633 ). The common sites of distant spread were bones (57.2%) in males and cervical lymph nodes (44.4%) in females (P = 0 . 106 ). Conclusion . Follicular thyroid cancer was the second common thyroid malignancy (35.0%) with a gradual rise in trend over the study period and male-female ratio of 1.5 : 1. Large anterior neck swelling was the commonest clinical presentation of FTC.